Луговые огневки рода Udea Gn. (Lepidoptera, Pyraustidae) запада Украины - Козакевич, 3.М. (Вестник зоологии, 1974)
Pyraloides moths of the genus Udea are presented nowadays in the Western regions of the Ukraine by 12 inhabiting species (U. ferrugalis, U. costalis, U. olivalis, U. prunalis, U. inquinatalis, U. decrepitalis, U. nebulalis, U. lutealis, U. elutalis, U. fulvalis, U. accolalis, U. alpinalis) and 3 doubtful ones (U. numeralis, U. uliginosalis, U. hamalis). Their distribution in the geographical zones and in the biotopes is presented. Mode of life. trophic connections and the time of appearance in nature are considered.